Status and Progress of Research on Metabolomics of Cervical Cancer - Shaojun CHEN; Ling GAN; Xinkang CHEN; Lingling XIONG; Die LONG; Lulu CHEN; Mengzhuan WEI; Li HUA; Haixin HUANG (Zhongliu Fangzhi Yanjiu)
Cervical cancer is one of the most common gynecological malignant tumors in China. Given their lack of obviously early symptoms, more than half of patients with cervical cancer are diagnosed in the middle and late stages of this malignancy, resulting in poor prognosis. Finding new therapeutic targets is the current research direction. Metabolomics, as a new omics technology, is expected to provide new targets for tumor precision diagnosis and treatment through the analysis of the changes and potential mechanisms of metabolites in tumor occurrence and development by chromatography, mass spectrometry, and other technologies. Herein, we review the research methods of metabolomics; metabolic characteristics of cervical cancer; and progress of the research on metabolomics in cervical cancer diagnosis, curative effect prediction, and prognosis evaluation to provide new ideas for the precise diagnosis and treatment of cervical cancer.